Systematic Review for the 2017 AHA/ACC/HRS Guideline for Management of Patients With Ventricular Arrhythmias and the Prevention of Sudden Cardiac Death: A Report of the American College of Cardiology/American Heart Association Task Force on Clinical Practice Guidelines and the Heart Rhythm Society. Issue 13 (25th September 2018) - Kusumoto, Fred M.; Bailey, Kent R.; Chaouki, Ahmad Sami; Deshmukh, Abhishek J.; Gautam, Sandeep; Kim, Robert J.; Kramer, Daniel B.; Lambrakos, Litsa K.; Nasser, Naseer H.; Sorajja, Dan
Abstract : Background: Although large randomized clinical trials have found that primary prevention use of an implantable cardioverter-defibrillator (ICD) improves survival in patients with cardiomyopathy and heart failure symptoms, patients who receive ICDs in practice are often older and have more comorbidities than patients who were enrolled in the clinical trials. In addition, there is a debate among clinicians on the usefulness of electrophysiological study for risk stratification of asymptomatic patients with Brugada syndrome. Aim: Our analysis has 2 objectives. First, to evaluate whether ventricular arrhythmias (VAs) induced with programmed electrostimulation in asymptomatic patients with Brugada syndrome identify a higher risk group that may require additional testing or therapies. Second, to evaluate whether implantation of an ICD is associated with a clinical benefit in older patients and patients with comorbidities who would otherwise benefit on the basis of left ventricular ejection fraction and heart failure symptoms. Methods: Traditional statistical approaches were used to address 1) whether programmed ventricular stimulation identifies a higher-risk group in asymptomatic patients with Brugada syndrome and 2) whether ICD implantation for primary prevention is associated with improved outcomes in older patients (>75 years of age) and patients with significant comorbidities who would otherwise meet criteria for ICD implantation on the basis of symptoms or left ventricular function. Results: Evidence from 6 studies of 1138 asymptomatic patients were identified. Brugada syndrome with inducible VA on electrophysiological study was identified in 390 (34.3%) patients. To minimize patient overlap, the primary analysis used 5 of the 6 studies and found an odds ratio of 2.3 (95% CI: 0.63–8.66; P =0.2) for major arrhythmic events (sustained VAs, sudden cardiac death, or appropriate ICD therapy) in asymptomatic patients with Brugada syndrome and inducible VA on electrophysiological study versus those without inducible VA. Ten studies were reviewed that evaluated ICD use in older patients and 4 studies that evaluated unique patient populations were identified. In our analysis, ICD implantation was associated with improved survival (overall hazard ratio: 0.75; 95% confidence interval: 0.67–0.83; P <0.001). Ten studies were identified that evaluated ICD use in patients with various comorbidities including renal disease, chronic obstructive pulmonary disease, atrial fibrillation, heart disease, and others. A random effects model demonstrated that ICD use was associated with reduced all-cause mortality (overall hazard ratio: 0.72; 95% confidence interval: 0.65–0.79; P <0.0001), and a second "minimal overlap" analysis also found that ICD use was associated with reduced all-cause mortality (overall hazard ratio: 0.71; 95% confidence interval: 0.61–0.82; P <0.0001). In 5 studies that included data on renal dysfunction, ICD implantation was associated with reduced all-cause mortality (overall hazard ratio: 0.71; 95% confidence interval: 0.60–0.85; P <0.001). Abstract : Supplemental Digital Content is available in the text.